Estrogen Receptors and Signaling in Fibroids: Role in Pathobiology and Therapeutic Implications. (September 2017) - Borahay, Mostafa A.; Asoglu, Mehmet R.; Mas, Aymara; Adam, Sarah; Kilic, Gokhan S.; Al-Hendy, Ayman
Uterine fibroids are the most common gynecologic tumors with a significant medical and financial burden. Several genetic, hormonal, and biological factors have been shown to contribute to the development and growth of fibroid tumors. Of these factors, estrogen is particularly critical since fibroids are considered estrogen dependent because no prepubertal cases have been described in the literature and tumors tend to regress after menopause. Understanding the role of estrogen in fibroids is not only important for understanding the pathobiology of fibroids but also for the development of successful therapeutics. In this review, we discuss the types and structure of estrogen receptors (nuclear and membrane bound, including α and β receptors and G protein-coupled estrogen receptor 1 GPER1). Estrogen-signaling pathways in fibroids include genomic (direct and indirect) and nongenomic including Ras-Raf-MEK (MAPK/Erk Kinase)-mitogen-activated protein kinase (MAPK) and phosphatidylinositide 3-kinase (PI3K)-phosphatidylinositol-3, 4, 5-trisphosphate (PIP3)-Akt (Protein kinase B)-mammalian target of rapamycin (mTOR) pathways; shortly Ras-Raf-MEK-MAPK and PI3K-PIP3-Akt-mTOR pathways. Several aberrations in estrogen receptors and signaling pathways are implicated in fibroid pathobiology. Current therapeutic and research agents targeting ERs/signaling include gonadotropin-releasing hormone (GnRH) agonists, GnRH antagonists, aromatase inhibitors, selective ER modulators, gene therapy, and others. Future research can identify potential targets for the development of novel treatments. In particular, epigenomics of estrogen activity and individualized (precision) medicine appear to be attractive areas for future research.